The effect of acute L-arginine supplementation on repeated sprint ability performance - Birol, Abdulkadir; Nişancı Kılınç, Fatma; Deliceoğlu, Gökhan; Keskin, Esra Dilek (Progress in Nutrition, 2019)
Aim: The aim of this study is to determine the effect of acute L-arginine supplementation on repeated sprint ability performance in football players aged between 18-21 years. Methods: The study was conducted on 20 volunteer healthy male football players playing in the under-21 football team in the 1st league of Turkey. General characteristics of football players were questioned and their anthropometric measurements were taken. The study was performed as a double-blind placebo-controlled design. Players were randomly given 0.15 g/kg/day relative dosage L-arginine or placebo with 500 ml of water 1 hour before repeated sprint ability test (RSAT). The 12x20m RSAT protocol was applied in the synthetic turf football field with a recovery interval of 30 seconds between each sprint and the photocell system was used to determine running time. Results: The mean age of the arginine group is 18.30±0.48 years and the mean age of placebo group is 18.33±0.50 years. 85% of the players never used L-arginine, and any dietary supplements. Only the ninth sprint time of the 12 sprints performed after the supplementation was 5.24% faster than the placebo group in the arginine group (p<0.05). However, no difference was detected between the groups in terms of sprint decrement score, total sprint time, blood pressure and heart rate (HR) (p>0.05). Conclusion: In this study, the supplementation of acute L-arginine administered to players had no significant effect on HR, blood pressure and RSAT total sprint time and sprint decrement score.